Diagnóstico en la gestión y administración de proyectos para Consorcios y Cooperativas Costarricenses - Sáenz-Arce, Carlos (Instituto Tecnológico de Costa Rica, 2012)
Despite of the success, Project management, within the literature and applicability is focused to known industrial sectors – information technology, construction, engineering, government – those considered as traditional in project management. This growth in project management is due to high importance strategic matters from top management, example, the management, organizational issues, effectiveness on human resources and costs and a positive impact to the organization or within community project is implemented. This work essentially is a qualitative investigation focused to various cooperative organizations with the objective to describe how project are administrated. The investigation was completed in four months and included auxiliary organizations – COOPRENA R.L. & URCOZON R.L., two base cooperatives - COOPELESCA R.L. & COOCIQUE R.L. and an expert within the costarrican cooperative field. The information is collected thru interviews to recognized and recommended cooperative experts to proceed next with the necessary data analysis. The cooperative sector has a huge importance and impact within the costarrican society and considered a motor at rural areas and most recently new emerging project with high visibility. This investigation incorporates the good practices described at PMBoK® del PMI® and tries to match or compare the information obtained thru surveys and evaluates the presence or not of the good practice within the project management against the reference from PMI.
Proyecto de Graduación ( Maestría en Gerencia de Proyectos ) Instituto Tecnológico de Costa Rica, 2012.
Keywords: Gestión de proyectos; Cooperativismo; Administración